1994
DOI: 10.1128/jvi.68.2.776-786.1994
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation at the carboxy terminus of the 55-kilodalton adenovirus type 5 E1B protein regulates transforming activity

Abstract: The 55-kDa product of early region lB (E1B) of human adenoviruses is required for viral replication and participates in cell transformation through complex formation with and inactivation of the cellular tumor suppressor p53. We have used both biochemical and genetic approaches to show that this 496-residue (496R) protein of adenovirus type 5 is phosphorylated at serine and threonine residues near the carboxy terminus within sequences characteristic of substrates of casein kinase II. Mutations which converted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 74 publications
3
51
0
Order By: Relevance
“…1B to be defective in the 289R-dependent block in accumulation of p53. Clearly, both mutant 55-kDa proteins were able to form complexes with E4orf6 at normal levels, in agreement with the finding that they induce host cell shutoff normally (59). These results also indicated that complex formation between E4orf6 and p53 is not sufficient to induce a reduction in p53 levels and that inhibition of p53 transactivation activity may be necessary.…”
Section: Fig 5 Analysis Of P53 Accumulation and E4orf6 Expression Isupporting
confidence: 87%
See 3 more Smart Citations
“…1B to be defective in the 289R-dependent block in accumulation of p53. Clearly, both mutant 55-kDa proteins were able to form complexes with E4orf6 at normal levels, in agreement with the finding that they induce host cell shutoff normally (59). These results also indicated that complex formation between E4orf6 and p53 is not sufficient to induce a reduction in p53 levels and that inhibition of p53 transactivation activity may be necessary.…”
Section: Fig 5 Analysis Of P53 Accumulation and E4orf6 Expression Isupporting
confidence: 87%
“…However, three observations argued strongly that generalized shutoff of host protein synthesis induced by complexes of E4orf6 and 55-kDa protein plays little or no role in the block in p53 accumulation. The first was that mutants pm490/1A and pm490/1/5A, which encode 55-kDa proteins lacking two or all three of the carboxy-terminal phosphorylation sites, fail to prevent the rise in p53 levels even though these mutant E1B products induce host cell shutoff effectively (59). Second, generalized host cell shutoff in infected 293 cells started over 7 h after the beginning of the decline in p53 levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…E1B from HAdV5 undergoes SUMOylation at lysine 104 and phosphorylation at the C‐terminal serine 490, serine 491, and threonine 495 (Fig A). Covalent addition of SUMO modulates protein–protein interactions, protein stability, and localization, and regulates many cellular processes, including DNA repair, antiviral responses, and tumor suppression .…”
Section: Structural and Functional Features Of E1b 55kmentioning
confidence: 99%